2012
DOI: 10.1186/1471-2407-12-329
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of aldehyde dehydrogenase isozymes in ovarian cancer tissues and sphere cultures

Abstract: BackgroundAldehyde dehydrogenases belong to a superfamily of detoxifying enzymes that protect cells from carcinogenic aldehydes. Of the superfamily, ALDH1A1 has gained most attention because current studies have shown that its expression is associated with human cancer stem cells. However, ALDH1A1 is only one of the 19 human ALDH subfamilies currently known. The purpose of the present study was to determine if the expression and activities of other major ALDH isozymes are associated with human ovarian cancer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 42 publications
2
43
0
Order By: Relevance
“…Although ALDH1A1 is regarded as a major form responsible for ALDH activity (19), other isoforms (ALDH1A3, ALDH3A2, and ALDH7A1) are also overexpressed in ovarian cancers (47). In fact, our data indicated that ALDH1A2 and ALDH3A2, in addition to ALDH1A1, may contribute to ALDH activity in #5.…”
Section: Discussionmentioning
confidence: 63%
“…Although ALDH1A1 is regarded as a major form responsible for ALDH activity (19), other isoforms (ALDH1A3, ALDH3A2, and ALDH7A1) are also overexpressed in ovarian cancers (47). In fact, our data indicated that ALDH1A2 and ALDH3A2, in addition to ALDH1A1, may contribute to ALDH activity in #5.…”
Section: Discussionmentioning
confidence: 63%
“…We and others previously demonstrated enhanced sphere forming and self-renewal ability of OCSCs when grown in stem cell-selective culture conditions (2629). To investigate the effect of SGI-110 on sphere formation, A2780 and A2780_CR5 cells were treated with SGI-110/CDDP alone or in combination, and tumor-sphere formation assays were performed.…”
Section: Resultsmentioning
confidence: 82%
“…Stromal and tumor cell expression of several isozymes was found to differ between normal tissue and ovarian tumors, as well as between OC of different histotype (124). …”
Section: Other Moleculesmentioning
confidence: 99%